Regenerative sustainability for the built environment – from vision to reality: an introductory chapter. (16th December 2015) - Zhang, Xiaoling; Skitmore, Martin; De Jong, Martin; Huisingh, Donald; Gray, Matthew
Abstract: Regenerative sustainability is emerging as an alternative discourse around the transition from a 'mechanistic' to an 'ecological' or living systems worldview. This view helps us to re-conceptualize relationships among humans' technological, ecological, economic, social and political systems. Through exploration of 'net positive' or 'regenerative' development lenses and the traditional sustainability literature, the conceptualization and approaches to achieve sustainable development and ecological modernization are expanded to articulate and to explore the evolving sustainability discourse, 'regenerative sustainability'. This Special Volume of Journal of Cleaner Production (SV) is focused upon various dimensions of regenerative sustainability (e.g. regenerative design, regenerative development, and positive development) applied to the urban built environment at scales, which range from individual buildings, neighbourhoods, and urban developments to integrated regional sustainable development. The main focus is on how these approaches and developments are evolving, how they can help us to prevent or adapt to climate change and how these approaches are likely to evolve in the next two to three decades. These approaches are addressed in four themes: (1) reviewing the theoretical development of the discourse of regenerative sustainability, its emerging principles and practices, (2) explaining how it can be measured and monitored, (3) providing encouraging practical pathways and examples of its implementation in multiple cultural and climatic contexts, and (4) mapping obstacles and enablers that must be addressed to help to ensure that more rapid progress is made in implementing the transitions towards an urban built environment that supports genuinely sustainable societies. Highlights: We investigate regenerative sustainability as a multi-faceted crystal with different aspects. The theory and definitions of the discourse is coloured by the ecological worldview. To engage developing appropriate metrics for Performance Assessment for regenerative concept. To elucidate pathways towards more regenerative sustainability models across different scales. Obstacle, benefit and enabler are explored with the metaphor of 'sticks', 'carrots' and 'sermons'.